ISRA’ILIYYAT DAN PENGARUHNYA TERHADAP KITAB KULLIYYAT RASA’IL AL-NUR KARANGAN SAID AL-NURSI - Baihaqi, Yusuf (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2016)
Al-Qur’an has been revealed to all mankinds as aguideline in their life. Al-Qur’an is revealed throughmutawatir method and is guaranted by Allah Almightyfrom any amendments. However there is exist themufassirun who has moulded their interpretationswith Isra’iliyyat. These elements are used wheneverthe mufassirun explains about the story of theprophets. Isra’iliyyat influence in tafseer is clearlyvisible, especially in the classical Qur’aniccommentators with the history-oriented. Isra’iliyyatalso gived visible effect on a contemporary tafseer"Kulliyat Rasa'il Al-Nur", written by an Islamicscholar and cleric from Turkey, Badi 'al-Zaman Al-Said Nursi. Although in some of his statements, hewas very harshly criticized Isra’iliyyat exist in anumber of books of tafseer. The exist of Isra’iliyyatcommentary in the "Kulliyat Rasa'il Al-Nur" verydiverse, but nevertheless the number of Isra’iliyyatquoted in the "Kulliyat Rasa'il Al-Nur" is little,compared with the other tafseer. This article willdiscuss further.